Smart energy meter based on hall effect current sensing techniques with IoT modules. Issue 1 (2nd January 2022) - Bansal, Dhruvi; Gupta, Kunal; Sharen Ganesh, M. C.; Goyal, Jayesh; Tharani, Kusum; Sharma, Sandeep
Abstract: The existing approach of an electrical board representative manually reading the energy metre and issuing invoices to the owner has been shown to be inefficient and prone to human mistakes and possibly misconduct. Indian energy users are also afflicted by a lack of current information and understanding. Using the IC ACS71020, this study presents a customized IoT-based Advanced Smart Energy Meter infrastructure with remote and local logging and monitoring of electrical parameters. The meter also has provisions for connections to both web and cellular internet using ESP8266 and GSMsim800a. The elimination of human interaction and the rapid updating of information makes the consumer's life easier and more efficient. Data is also shown on an OLED screen and stored on an SD Card / Flash Memory, allowing access to a local server.